Prevalence of Pediculosis Capitis and its Risk Factors in Elementary School Students - I Made Sudarmaja (Journal of Global Pharma Technology, 2016)
Background: Pediculosis capitis or head-lice infestation is a health problem, especially in children in developing countries. Transmission of pediculosis capitis is also fast, causing a high-incidence in an area. This study was conducted to determine the prevalence of pediculosis capitis and the relationship between risk factors for its infestation. Methods: This is a descriptive study with a cross-sectional design. The data was collected from elementary school students in Tenganan village, Bali, Indonesia in September 2018. The sampling technique was a voluntary sampling method with a sample of 141 elementary school students. Data analysis was carried out with the SPSS with univariate and bivariate analysis. Results: The prevalence of pediculosis capitis in elementary school children in Tenganan Village is 69.5%. Factors related to pediculosis capitis infestation are sex (PR=2.235, p <0.001), long-hair (PR=2.015, p <0,001), shared hair-accessories (PR=1.450, p=0.004), and lived with people infected with head lice (PR=1.692, p <0.001). Conclusion: The prevalence of pediculosis capitis in elementary school children in Tenganan Village is 69.5% with gender as the most influential risk factor for infestation.Keywords: Pediculosis capitis, Prevalence, Risk factors.